Executive capacity to control legislatures and presidential choice of cabinet ministers in East Asian democracies - Lee, Don S. (Wiley, 2018)
How do presidents in new democracies choose cabinet ministers to accomplish their policy goals? Contrary to existing studies explaining the partisan composition of the cabinet with institutional characteristics, such as formal authority, we argue that the broader political context surrounding the president's ability to control the legislature can affect cabinet partisanship. By analyzing original data on cabinet formation in all presidential systems in East Asia since democratization, we find that when presidents are more likely to be dominant in executive-legislative relations, they have less concern about legislative support and more leeway to focus on policy performance by appointing nonpartisan cabinet members. This analysis suggests that understanding cabinet partisanship requires a view of cabinet appointments as a trade-off between securing legislative support and managing policy performance, and the scope of this compromise depends on the strength of the president vis-à-vis the legislature.